Oscillation of arbitrary-order derivatives of solutions to linear differential equations taking small functions in the unit disc - Pan Gong; Li-Peng Xiao (Electronic Journal of Differential Equations, 2015)
In this article, we study the relationship between solutions and their derivatives of the differential equation $$ f''+A(z)f'+B(z)f=F(z), $$ where $A(z), B(z), F(z)$ are meromorphic functions of finite iterated p-order in the unit disc. We obtain some oscillation theorems for $f^{(j)}(z)-φ(z)$, where f is a solution and $φ(z)$ is a small function.